A scientific contribution to legume studies during the fifty years of the Institute of Animal Science - Ruiz, Tomás E.; Febles, Gustavo; Alonso, J. (Cuban Journal of Agricultural Science, 2016)
Papers published in the Cuban Journal of Agricultural Science between 1967 and 2013 dealing with creeping, seasonal and shrub legumes are reviewed. Among them are those about the state of the art on this subject, representing a total of 257 contributions. Outstanding are the investigations on Neonotonia wightii, Leucaena leucocephalala and the multiple associations of creeping legumes with grasses, which allowed defining technologies for their establishment and exploitation in grazing systems for animal production. Work developed with this plant family also contributed with a technology for biomass production of seasonal legumes for feeding non-ruminant animals.Key words: creeping legumes, shrub, tree